Research on BIM collaborative design for the outdoor integrated pipeline of a rail transit depot - Wu, Honghua; Xu, Jiuyong; Jin, Yongle; Li, Qiang; He, Wei; Zhang, Panfeng; Zhang, Jie; Li, Jianan (Journal of physics. Conference series, 2023)
The outdoor integrated pipelines of rail transit depots have many specialties, many interfaces, and complex cross-relationships, which are the key and difficult points of depot design. The traditional outdoor integrated pipeline design method has the disadvantages of a large amount of data calculation, error-prone, and low drawing efficiency. At present, the use of BIM technology for auxiliary design also has difficulties, such as slow modeling speed, inconvenient collaborative design, and low efficiency of 3D conversion of 2D drawings. Based on Revit software, this paper focuses on the specific implementation scheme of BIM collaborative design of outdoor integrated pipelines in depots to solve the appealing problem. Overcame a number of key technologies independently developed, such as depot family library construction, Dynamo visual programming track rapid modeling, and GLS rapid drawing software. Realization of outdoor Comprehensive pipeline rapid modeling, collision optimization, and 2D rapid plotting. And it has been applied in an overhaul and heavy repair depot in the southwest, which has greatly improved the design efficiency and quality of outdoor integrated pipelines. The research result can provide a theoretical reference for the BIM collaborative design of the outdoor integrated pipeline of the depot.